Ammonium Carbamate Functionalization of Microgels for pH‐Sensitive Loading and Release of Anionic and Cationic Molecules. Issue 1 (12th November 2013) - Behra, Muriel; Hartmann, Laura
<x xml:space="preserve">Abstract</x> The functionalization of porous microgels with polyamines is presented along with their partial conversion into carbamates with CO2 for an efficient loading and release via electrostatic interactions. The resulting ammonium carbamate particles switch their charge from negative at pH 10 to positive at pH 5 and present a zwitterionic state at pH 7. Thus, they can easily be loaded with both cationic and anionic molecules. Furthermore, the ammonium carbamate functionalization allows for an efficient release at pH values between 5.0 and 7.4, whereas classical functionalization with carboxy‐ or amine‐groups requires pH values below pH 4 or above pH 9. This versatile and easy‐to‐install functionalization has a great potential for various applications, such as the loading and release of drugs or nanoparticles from hydrogels. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>